PENGARUH LABA BERSIH DAN KOMPONEN ARUS KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR INFRASTRUKTUR, UTILITAS, DAN TRANSPORTAS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Aribowo, Fajar; Tombilayuk, Andriani (PRIMA EKONOMIKA, 2020)
This study aims to analyze and test information regarding information on net income and cash flow components of share prices in infrastructure, utility, and transportation sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The research method used in this research is quantitative method. The sample used in this research is infrastructure, utility and transportation companies listed on the Indonesia Stock Exchange by using purposive sampling in order to obtain 14 companies. To determine the effect of net income and cash flow components used linear regression analysis, no coefficient analysis, partial hypothesis testing, simultaneous hypothesis testing and determination coefficient analysis (R2). The analysis tool used is the SPSS version 25 program. The results of research that have been carried out using linear multiple analysis t test and F test. The t test in this study shows that net income has an effect on stock prices. The cash flow component has no effect on stock prices. The F test in this study shows that net income and cash flow components have an effect on stock prices. Keywords: Net Profit, Cash Flow Components, Stock Prices.